Florıstıc And Systematıc Analysıs of The Composıtıon of Algoflora Of The Sangzar Rıver - Ismatova Zulaykho Asadovna (International Journal of Advanced Science and Technology, 2020)
According to the results of the study, 522 species and varieties belonging to 100 genus, 48 families, 24 orders, 14 classes, 7 divisions were discovered in the Sangzar River, of which Cyanophyta - 56, Rhodophyta - 2, Xanthopyta - 7, Chrysophyta - 2, Bacillariophyta - 355, Euglenophyta - 15, 85 - Chlorophyta was discovered for the first time.